2014
DOI: 10.7314/apjcp.2014.15.18.7863
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Retinoblastoma Patients in Malaysia

Abstract: Background: Retinoblastoma is a rare type of cancer that usually develops in early childhood. If left untreated it can cause blindness and even death. The aim of this study is to determine sociodemographic and clinical features of retinoblastoma patients and also to determine the treatment pattern and outcome in Malaysia. Materials and Methods: Data for this study were retrieved from the Retinoblastoma Registry of the National Eye Database (NED) in Malaysia. Hospital Kuala Lumpur, Hospital Umum Kuching, Sarawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
11
13
2
Order By: Relevance
“…The proportion of cases with the extraocular disease in our study was 41%, which was significantly higher than the developed world (less than 5%) . This is comparable to the reports from developing (Taiwan, Malaysia) and underdeveloped regions (Ghana) of the world which ranges from 26% to 50% . Major reasons for late presentation with advanced disease include lack of awareness, inadequate healthcare facilities, unreliable referral system, delay in seeking health care by the guardians, and poor compliance to treatment because of fear of morbidity and treatment failure …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The proportion of cases with the extraocular disease in our study was 41%, which was significantly higher than the developed world (less than 5%) . This is comparable to the reports from developing (Taiwan, Malaysia) and underdeveloped regions (Ghana) of the world which ranges from 26% to 50% . Major reasons for late presentation with advanced disease include lack of awareness, inadequate healthcare facilities, unreliable referral system, delay in seeking health care by the guardians, and poor compliance to treatment because of fear of morbidity and treatment failure …”
Section: Discussionsupporting
confidence: 64%
“…This was higher when compared with other studies from Asia, which report the average/median age at diagnosis from 22 months to 29 months. However, this is better when compared with reports from the African continent where the median age at diagnosis was 36 months (Ghana) and 37.5 months (Kenya) …”
Section: Discussioncontrasting
confidence: 59%
“…To our knowledge, the present analysis is the first to show that Korean retinoblastoma patients diagnosed at less than 1 year of age showed a tendency to be classified in a lower IIRC stage than did those diagnosed at an older age and that the age at diagnosis is significantly positively correlated with IIRC stage. In a similar context, a few recent studies reported in other parts of Asia showed that a higher proportion of patients with bilateral retinoblastoma rather than unilateral retinoblastoma were diagnosed at an earlier IIRC stage [12,13]. As in our study, these studies also showed that patients diagnosed at an age younger than 1 year were more likely to have bilateral retinoblastoma rather than unilateral retinoblastoma [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…In a similar context, a few recent studies reported in other parts of Asia showed that a higher proportion of patients with bilateral retinoblastoma rather than unilateral retinoblastoma were diagnosed at an earlier IIRC stage [12,13]. As in our study, these studies also showed that patients diagnosed at an age younger than 1 year were more likely to have bilateral retinoblastoma rather than unilateral retinoblastoma [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…Proptosis, which is a late sign of RB, is still common in developing countries compared with developed countries (Dimaras et al, 2012). In addition, glaucoma and hyphema may mimic RB (Subramaniam et al, 2014). Other presentations can be as a fungating and necrotic orbital mass, buophthalmos with an enlarged and cloudy cornea or with a flat anterior chamber (Essuman et al, 2010).…”
Section: Clincial Presentationmentioning
confidence: 99%